Combining active seismic data from Apollo 14 and 16 with ground penetrating radar results to examine the shallow lunar subsurface. (May 2022) - Martella, Chloe Helene; Mattei, Elisabetta; Lauro, Sebastian Emanuel; Cosciotti, Barbara; Pettinelli, Elena
Abstract: The Active Seismic Experiments conducted during the Apollo 14 and 16 missions represented the first attempt to perform an off-Earth refraction seismic survey. The collected seismic traces have been analyzed by several authors and a two-layer structure has been suggested. The top layer consists of regolith, however the nature of the underlying material is still debated because the measured velocity is too low for a competent or even intensely fractured rock layer. Here we propose a new approach that combines refraction seismic and Ground Penetrating Radar (GPR) data to better constrain the underlying geological units. Given the relative uniformity of the shallow lunar subsurface and the interpretation of GPR data acquired at Von Kármán crater, we assumed that the second layer at the Apollo 14 and 16 landing sites is a mixture of fine materials and rocks. To assess this hypothesis we first reanalyzed the active seismic traces and computed the compressional wave velocities in the first and second layers, obtaining v 0 = 116 ± 5 m s − 1 and v 1 = 298 ± 52 m s − 1 at the Apollo 14 landing site and v 0 = 122 ± 3 m s − 1 and v 1 = 332 ± 23 m s − 1 at the Apollo 16 landing site. Second, we used a time-average model and laboratory data on the compressional wave velocity in lunar rocks to estimate the rock volume fraction that reproduces the overall compressional wave velocity in the second layer, with values ranging from 20 to 60% and 25 to 60% for the Apollo 14 and 16 landing sites, respectively. Finally, we used the rocks/fine materials ratio to estimate the overall dielectric constant of the second layer, which varies between 3.9 and 5.5. These results are in very good agreement with recent re-analysis of electromagnetic and seismic data collected at the Apollo 17 site and suggest that an ejecta deposit below the regolith might be common to all three sites. Highlights: Combination of seismic and GPR data can better constrain lunar subsurface units. An ejecta deposit below the regolith is inferred at Apollo 14 and 16 landing sites. The ratio of fine materials and rock inclusions in the second layer is computed. Rocks/fine materials ratio allows to estimate the second layer dielectric constant. Moon shallow subsurface structure might be common at Apollo 14, 16 and 17 sites.